Comments on 'comparison of architectures and robustness of model reference adaptive controllers and L1‐adaptive controllers'. (15th June 2015) - Ortega, Romeo; Panteley, Elena; Bobtsov, Alexey
Summary: In a recent paper it is claimed that adding a filter at the plant input to a classical direct model reference adaptive control constitutes a 'new architecture' for adaptive control. The purpose of this note is to show that this claim is specious. Towards this end, we bring to the readers attention the some recent results where a rigorous mathematical analysis shows that the resulting control signal always converges to the output of a linear time‐invariant proportional plus integral (PI) controller, whose gains are independent of the plant parameters. Moreover, it is shown that if the PI controller does not stabilize the plant, the proposed controller will not stabilize it either, making unnecessary the addition of the adaptation. Copyright © 2015 John Wiley & Sons, Ltd.